Silver Nanoparticles and Graphene Oxide Complex as an Anti-Inflammatory Biocompatible Liquid Nano-Dressing for Skin Infected with Staphylococcus aureus - Zielińska-Górska M; Sosnowska-Ławnicka M; Jaworski S; Lange A; Daniluk K; Nasiłowska B; Bartosewicz B; Chwalibog A; Sawosz E (Dove Medical Press, 2023)
Marlena Zielińska-Górska,1 Malwina Sosnowska-Ławnicka,1 Sławomir Jaworski,1 Agata Lange,1 Karolina Daniluk,1 Barbara Nasiłowska,2 Bartosz Bartosewicz,2 André Chwalibog,3 Ewa Sawosz1 1Department of Nanobiotechnology, Institute of Biology, Warsaw University of Life Sciences, Warsaw, 02-787, Poland; 2Institute of Optoelectronics, Military University of Technology, Warsaw, 00-908, Poland; 3Department of Veterinary and Animal Sciences, University of Copenhagen, Frederiksberg, 1870, DenmarkCorrespondence: Marlena Zielińska-Górska, Department of Nanobiotechnology, Institute of Biology, Warsaw University of Life Sciences, Ciszewskiego 8 St., bldg. 23, room 110, Warsaw, 02-786, Poland, Tel +48225936665, Email marlena_zielinska_gorska@sggw.edu.plBackground: Bacterial skin infections, including Staphylococcus aureus, are a powerful and still not fully resolved problem. The aim of this research was to determine the possibility of using a complex of graphene oxide (GO) encrusted with silver nanoparticles as an effective antibacterial agent against S. aureus and to assess its pro-inflammatory properties.Methods: The tests were carried out in vitro on EpiDerm™ Skin, an artificial skin model (MatTek in vitro Life Science Laboratories, Slovak Republic), and the fibroblast cell line (HFF-2 from ATCC, USA). Both models were infected with S. aureus bacteria (ATCC 25923) and then treated with antibiotics or our experimental factors: silver nanoparticles (AgNPs, Nano-koloid, Poland), graphene oxide (GO, NanoPoz, Poland), and complex AgNP-GO (hydrocolloid created by self-assembly).Results: The antibacterial effectiveness of the AgNP-GO complex was equivalent to that of the antibiotic. In addition, an increase in the level of pro-inflammatory cytokines was observed under the influence of antibiotic administration, in contrast to the effect of AgNP-GO, which showed very limited pro-inflammatory activity.Conclusion: Hydrocolloid of the AgNP-GO complex, administered in the form of a liquid dressing, may act as an antibacterial agent and also reduce inflammation induced by S. aureus infection.Keywords: human skin, inflammation state, nanomaterials, antibacterial properties